PENGARUH INTERNAL DAN EXTERNAL LOCUS OF CONTROL TERHADAP PRESTASI USAHA MIKRO KECIL MENENGAH KABUPATEN SAMPANG - Bambang Sudarsono; S Anugrahini Irawati (Eco-Entrepreneur, 2016)
This study aims to determine the role of personality traits (locus of control), the need to excel and achieve competitive advantage enterprenurship Small and Medium Enterprises (SMEs). The population in this study is the owner / manager / staff of companies (SMEs) in Bangkalan. The sampling technique is convenience sampling, that is, those who successfully met and willing to become respondents in this study. The analysis tool used is the Multiple Linear Regression Analysis to determine how much influence the independent variables (X1 and X2) to the dependent variable (Y) where the test results hypothesis that the Internal Lucos of Control and External Lucos of Control which is owned by SMEs Sampang together -Same significant effect with the amount of determination coefficient of 50.01% with a suggestion to change the orientation of External Lucos of Control into SMEs oriented Lucos of Internal Control in a way to optimize the ability of self-owned through inrcresing creativity, creativity, motivation and itsself.